Simulation and Design of Biological Shield for the 115 kJ IR-MPF-100 Plasma Focus Device Using MCNP Code - Babaei, Morteza; Sadighzadeh, Asghar; Kiashemshaki, Maryam; Vosoghi, Sara; Zaeem, Alireza Asle; Kasesaz, Yaser; Rezaeifard, Behzad; Damideh, Vahid (Springer US, 2016)
The paper reports on the design of biological neutron shielding for IR-MPF100 plasma focus device which recently has been designed and constructed in plasma physics and nuclear fusion research institute. Plasma focus devices are known as pulsed intense sources of ionizing radiations such as hard X-ray and fast neutrons as a result of the formation of a hot dense plasma column then acceleration of energetic ions and electrons in the opposite directions. Therefore, taking into account a biological shield particularly for the operators of the PF device as radiation workers is crucial. Analytical calculations on the maximum permissible effective dose for radiation workers (for whole-body exposure) allow below 200 shots/year for IR-MPF100 operating at its nominal 115 kJ capacitor bank energy without any shielding wall. In order to decrease the personnel absorbed radiation dose and increase the maximum allowed shot per year the design considerations for a biological shield has been recognized using MCNP4C code. Our calculations was based on the effect of ordinary concrete, polyethylene mixed with 30 % natural boron and solid boric acid on the decrement of the absorbed dose. These calculations represent that using a double layer shield consists of 30 cm width of pure polyethylene as well as 10 cm lead, ends in appropriate decrement of the effective dose per shot from 0.1 mSv to 1.2 µSv, therefore increases the allowed usage of the device up to 15,600 annual shots.